The challenges presented by parental mental illness and the potential of a whole‐family intervention to improve outcomes for families. Issue 1 (18th August 2015) - Gatsou, Lina; Yates, Scott; Goodrich, Nigel; Pearson, Dan
Abstract: Parental mental illness (PMI) can negatively affect the lives of all family members, and there is acknowledged need to work with family and social contexts to promote recovery. However, programmes undertaking such work remain rare and knowledge concerning mechanisms through which PMI impacts families and through which recovery might be achieved is underdeveloped. This paper outlines a new family intervention programme and presents evidence from focus groups with 16 professionals into their experiences of work with families with PMI. Evidence suggests that interactional effects of PMI, family communication and family relationships are key to understanding its impacts, but professionals are liable to struggle to engage with these due to concerns over stigma, lack of skills and low confidence. Positive impacts on practice were achieved through raising awareness of the whole‐family context in relation to PMI, building confidence to raise and engage with PMI and the provision of structured tools for use with families. Positive impacts on the lives of family members were then achieved by professionals in relation to symptoms for the ill parent, the burden on children and overall family well‐being, strongly mediated through improved family communication, understanding and relationships. Implications for policy and practice are considered.